Mesh tied to rope, Phonse Ducey's twine store, Keels, NL - Whitney, Erin (2012)
Phonse Ducey demonstrates how to attach mesh to a rope in his twine store in Keels, NL. On the left, mesh is tied on at every third hole, appropriate for gill nets. On the right, the mesh is tied on at each hole for a cod trap, since that type of net would have to withstand greater pressure.